Hidden colon adenocarcinoma diagnosed from mouth metastasis: case report and literature review - de Almeida Lança, Maria Leticia [UNESP]; Carvalho, Yasmin Rodarte [UNESP]; Almeida, Janete Dias [UNESP]; Kaminagakura, Estela [UNESP] (Springer Nature, 2023)
Background: We report an unusual case of metastatic colon adenocarcinoma to the maxilla as an initial clinical sign of the disease, this being the second case reported in the palate. In addition, we show an extensive review of the literature, with clinical cases of adenocarcinoma with metastasis to the mouth. Case presentation: An 80-year-old man complained of “swelling on the palate” with a 3-week evolution time. He reported suffering from constipation and high blood pressure. The intraoral examination revealed a pedunculated, red, and painless nodule on the maxillary gingiva. Under the diagnostic hypotheses of squamous cell carcinoma and malignant neoplasm of the salivary gland, an incisional biopsy was performed. Microscopically, the columnar epithelium was observed forming papillary areas, neoplastic cells with prominent nucleoli, hyperchromatic nuclei, atypical mitotic figures, and mucous cells, being positive for CK 20, suggesting the provisional diagnosis of metastatic adenocarcinoma, probably of gastrointestinal origin. The patient was submitted to endoscopy and colonoscopy exams, and a lesion in the sigmoid region of the colon was observed. After a colon biopsy, a moderately differentiated adenocarcinoma was confirmed, establishing the final diagnosis of metastatic neoplasia of colon adenocarcinoma to the oral lesion. The literature review revealed 45 clinical cases of colon adenocarcinoma with metastasis to the oral cavity. To the best of our knowledge, it is the second case on the palate. Conclusions: Colon adenocarcinoma with metastasis to the oral cavity is rare but should be included in the differential diagnosis of neoplasms of the oral cavity, even when there are no known primary tumors in some cases, and this may be the first indication of the presence of a tumor.
Keywords: Adenocarcinoma; Maxilla; Neoplasm metastasis